2016
DOI: 10.1186/s12886-016-0298-x
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of capillary dropout in the deep retinal capillary plexus using optical coherence tomography angiography in a patient with Purtscher’s retinopathy exhibiting normal fluorescein angiography findings: a case report

Abstract: BackgroundFat embolism in the deep retinal capillary plexus is one of the reported mechanisms underlying central/paracentral scotoma in patients with Purtscher’s retinopathy. Here we report the clear delineation of capillary dropout in the deep capillary plexus using optical coherence tomography angiography (OCTA) in a chronic case of unexplained scotoma that developed after femoral fracture. The patient exhibited normal fluorescein angiography (FA) findings and a normal retinal appearance.Case presentationA 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…An interesting finding was noted by Tokimitsu et al . [8] in their report of a 42-year-old Japanese male patient who suffered a femoral fracture. They noted capillary drop-out only in the deep capillary plexus with no changes in the superficial plexus.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding was noted by Tokimitsu et al . [8] in their report of a 42-year-old Japanese male patient who suffered a femoral fracture. They noted capillary drop-out only in the deep capillary plexus with no changes in the superficial plexus.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the present study showed that the image quality obtained from the OCTA device, RTVue-XR Angiovue, was high and was sufficient for analysis using the built-in image analysis software. This technology has improved the visualization of retinal capillaries and micro-angiopathic features, and offers great potential for the study and quantification of retinal microvascular attributes such as vessel density, branching pattern, capillary tortuosity, vasodilation, microaneurysms, and vascular remodeling in both healthy and diabetic subjects [ 14 – 16 ]. The vessel densities of SCP and DCP were lower in diabetic eyes compared with control eyes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with the previous report of a chronic Purtscher retinopathy case. 4 Besides, we also detected the disturbance of macular ellipsoid zone from widefield swept-source optical coherence tomography, which might be associated with a poor visual acuity. In conclusion, optical coherence tomography–based multimodal imaging can be used to visualize capillary nonperfusion, quantify foveal avascular zone, and detect ellipsoid zone defect in acute Purtscher retinopathy.…”
mentioning
confidence: 75%